Pendampingan UMKM Batik Wangsa Singhasari Dalam Pencapaian SDGs 8 - Darmadji; Kiyono (Fakultas Teknik, Universitas PGRI Banyuwangi, 2026)
This community service program aims to strengthen the role of local wisdom–based batik MSMEs in supporting Sustainable Development Goal (SDG) 8 on decent work and economic growth. The program was conducted at Batik Wangsa Singhasari (BWS), Randuagung Village, Singosari District, Malang Regency, as a continuation of previous assistance implemented in 2022. Field observations prior to the 2025 program revealed a decline in production continuity, weak marketing practices, and limited institutional management. The novelty of this program lies in shifting the empowerment approach from technical batik skills improvement toward strengthening production management, marketing management, and institutional sustainability aligned with SDG 8. The method employed was continuous mentoring (backstopping) combined with limited capital stimulation. The results showed significant improvements, including regular batik production and sales from September to December 2025, amounting to 10 sarongs, 5 long cloths, 5 scarves, and 14 tumpal motifs, with an additional order of 40 tumpal motifs in December. Furthermore, a new organizational structure of BWS was established, a joint batik workspace and gallery were set up at Rumah Seni Budaya Batik (RSBS), and regular weekly production meetings were agreed upon. These outcomes indicate that management-based empowerment can enhance MSME sustainability and contribute effectively to the achievement of SDG 8 through local creative industries.